THIN NITRIDE LAYERS AS PERMEATION BARRIERS - Jakub Veverka; Jiri Matejicek; Frantisek Lukac; David Pospisil; Ladislav Cvrcek; Vincenc Nemanic (Acta Polytechnica CTU Proceedings)
Permeation barriers represent one of the crucial fields in materials development for thermonuclear fusion. Primary objective of the barriers is to suppress the permeation of hydrogen isotopes (mainly tritium) from future thermonuclear fusion facilities. Secondary objective is to reduce hydrogen retention in structural materials, potentially also improving their corrosion resistance. Expected reactor conditions put high demands on the material, as well as on the final barrier quality. Key properties are tritium permeation reduction, absence of defects (especially cracks), high-temperature stability and corrosion resistance, and compatibility with structural materials (mostly ferritic-martensitic steels). Regarding industrial scale production, ability of the deposition method to coat large complex surfaces is desirable. Thin nitride layers, identified as promising permeation barriers, were prepared by diffusion-based nitridation and physical vapour deposition (PVD) and characterized.